Analysis of the tomato leaf transcriptome during successive hemibiotrophic stages of a compatible interaction with the oomycete pathogen Phytophthora infestans. (8th May 2015) - Zuluaga, Andrea P.; Vega‐Arreguín, Julio C.; Fei, Zhangjun; Matas, Antonio J.; Patev, Sean; Fry, William E.; Rose, Jocelyn K. C.
Summary: The infection of plants by hemibiotrophic pathogens involves a complex and highly regulated transition from an initial biotrophic, asymptomatic stage to a later necrotrophic state, characterized by cell death. Little is known about how this transition is regulated, and there are conflicting views regarding the significance of the plant hormones jasmonic acid (JA) and salicylic acid (SA) in the different phases of infection. To provide a broad view of the hemibiotrophic infection process from the plant perspective, we surveyed the transcriptome of tomato ( Solanum lycopersicum ) during a compatible interaction with the hemibiotrophic oomycete Phytophthora infestans during three infection stages: biotrophic, the transition from biotrophy to necrotrophy, and the necrotrophic phase. Nearly 10 000 genes corresponding to proteins in approximately 400 biochemical pathways showed differential transcript abundance during the three infection stages, revealing a major reorganization of plant metabolism, including major changes in source–sink relations, as well as secondary metabolites. In addition, more than 100 putative resistance genes and pattern recognition receptor genes were induced, and both JA and SA levels and associated signalling pathways showed dynamic changes during the infection time course. The biotrophic phase was characterized by the induction of many defence systems, which were either insufficient, evaded or suppressed by the pathogen.